OPTIMALISASI PEMASARAN PRODUK WISATA SERTA PENGUATAN EKONOMI LOKAL DAN KESADARAN MASYARAKAT DI PULAU TIDUNG KEPULAUAN SERIBU PROVINSI DKI JAKARTA - Achmad Tarmizi; Agung Solihin (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2023)
This study aims to optimize the marketing of tourism products on Tidung Island, Thousand Islands, DKI Jakarta Province with the aim of increasing the local economy and public awareness. Tidung Island has great tourism potential, but there are still obstacles in marketing and active community participation in developing the local economy. The research methods used were surveys, interviews, and direct observation. The data collected includes information about tourist profiles, marketing strategies that have been implemented, as well as inhibiting factors in local economic development. In order to optimize the marketing of tourism products, the recommended strategic steps include developing attractive tour packages, skills training for local communities, and establishing a tourist information center. In addition, collaboration between local governments, local business actors and the community is key in achieving the goal of strengthening the local economy and community awareness. This research is expected to provide input and recommendations for local governments, businesses, and the community in increasing the marketing of tourism products on Tidung Island, so that it can have a positive impact on the local economy and local community awareness.